Durability of carbon fibre reinforced polymer laminates - Fonseca, S. Cabral (2011)
Due to their excellent mechanical properties and easy application Carbon Fibre Reinforced Polymers (CFRP) are being successfully used to repair and renew old and damaged civil engineering infrastructures. In particular, the method of strengthening concrete members with externally bonding of CFRP laminates has become increasingly popular. In fact, extensive research has shown that this technique can lead to a substantial improvement in the fl exural and shear strength capacities of the member repaired. In such applications, materials involved will be exposed to outdoor environmental conditions, including humidity, water from rain, saline-water, ground water and high alkalinity solutions due to chemical composition of the concrete itself, as well as solar ultraviolet (UV) radiation. Thus, it is of great relevancy to study the durability of the materials involved, namely epoxy adhesives and CFRP laminates, as well as, the integrity of the entire system, when subjected to those environmental factors. This work is part of a much larger research study to predict the long-term behaviour of several commercial CFRP laminate/adhesive systems used in the rehabilitation of concrete structures. In the whole project it is recognised that the durability of these solutions depends not only on the durability of the composite materials but also on the performance of the systems used to bond them to the concrete. This present document provides details about the durability of CFRP laminates and the study carried out to investigate the environmental and accelerated ageing effects on three types of commercially available CFRP laminates. The changes in CFRP laminates properties after exposure up to 18 months under different environmental conditions – immersion in demineralised water, saline and alkaline solutions at room temperature, 40 ° C and 60 °C, as well as under constant humidity condensation atmosphere at 40 ° C – are reported and discussed. The results of tests performed in accelerated weathering chambers – with UV radiation – are also included. Results obtained offer valuable information about the progression of material degradation under different ageing conditions (some of them accelerated), which can be used, not only to characterise the behaviour of CFRP laminates, but also for a better understanding of the degradation mechanisms involved, which is a base for the design of service life-prediction models.